Providing a Professional Ethics Model for Improving Public Accountability in the Iranian Governmental Organizations - Sfestani, Rasool Sarihi; Peykani, Mehraban Hadi (International Review of Management and Marketing, 2017)
Today, as a result of the concept of professionalism, diversity and the intertwining professions and many challenges arising from globalization, professional ethics strategic position in a global environment of business in other words go beyond the range of scientific fields have raised vast knowledge. On the other hand, in the modern era accountability is one of the requirements of the new rule and if leads to come true strengthen genuine relationship - between citizens and lawyers, and brokers, increasing the effectiveness and transparency in organizational performance, reduce corruption (financial, administrative, etc.), enhancing the coherence and legitimacy of the political system will lead. In this research first define and describe aspects of professional ethics (individual, organizational and extra organizational) and public accountability (moral, legal, financial, political, and social performance). Then, through scientific studies and library, 198 indicators were classified in the framework of professional ethics to enhance public accountability that with applying defined indicators of professional ethics can effort to the promotion of all aspects of public accountability; In other words, with the sovereignty of professional ethics, in the remarkable amount will cause to reduce tensions and success in achieving the target and will cause the promotion of public accountability and government agencies. Keywords: professional ethic, public accountability, moral accountability, social accountability, legal accountability, financial accountability. JEL Classifications: C52, C32, Q13